SEJARAH PERKEMBANGAN TAFSIR ALQURAN PASCA KEMERDEKAAN DAN KONTEMPORER (1945-2000-an) - Syamsuddin, Lukman; Abu Bakar, Achmad; Mardan, Mardan (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
This article focuses on the history of development interpretation of the Qur'an in Indonesia, both post independence as one of the discussions presented to enthusiasts and study of understanding the Qur'an. The type of this research is a literature review and the use of content analysis (content analysis). Formulate of the problem this research is how the history of the development interpretation of the Qur'an in post-independence and contemporary Indonesia? In this study, it concluded that the study of the understanding of the Qur'an in the archipelago, especially Indonesia, continued to develop according to the times so that various works of scholars were born in the field of Qur'anic interpretation using multiple methods..